Des modes d’existence de l’œuvre littéraire médiévale : Genette peut-il aider les philologues ? - Florent Coste (Perspectives Médiévales)
The ontology of art is interested in the modes of existence of the work of art. With L’Œuvre de l’art, Gérard Genette came up with a fascinating and seminal contribution to this type of philosophy. But medieval textuality plunges us into trouble : medieval literary works offer a lot of thorny cases, which Genette can help to describe better. What is an artwork with multiple and competing versions ? What is the artwork of a collection whose witnesses are fragmentary and lacunar ? Is it possible to distinct continuations and sequels from the works they complete or supplement ? Is a medieval translation, unlike a modern one, a different artwork from the original ? Does philology consist in converting medieval textuality into the ontological regime of the printed word ? This contribution argues that Genette’s perspective can bring some of the benefits of the analytic aesthetics to enrich the conception of medieval textuality and clarify some of the most difficult debates.